AbrB modulates expression and catabolite repression of a Bacillus subtilis ribose transport operon. - Strauch, M A (1995)
A Bacillus subtilis ribose transport operon (rbs) was shown to be subject to AbrB-mediated control through direct AbrB-DNA binding interactions in the vicinity of the promoter. Overproduction of AbrB was shown to relieve catabolite repression of rbs during growth in the presence of poorer carbon sources such as arabinose but had much less effect when cells were grown in the presence of glucose, a rapidly metabolizable carbon source. A ccpA mutation relieved catabolite repression of rbs under all conditions tested. One of the AbrB-binding sites on the rbs promoter contains the putative site of action for the B. subtilis catabolite repressor protein CcpA, suggesting that competition for binding to this site could be at least partly responsible for modulating rbs expression during carbon-limited growth.